THE IMPLEMENTATION OF ZTYPE GAMES TO LEARNING VOCABULARY FOR ENGLISH STUDENTS - Hartono, Steven Christover; Nugrahini, Yulia (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2023)
ZTYPE games are one of the good learning media to be used in teaching vocabulary. The researcher conducted this research to answer the formulation of the research problem, how is the student perspective and develop vocabulary learning using ZTYPE games. And aims to describe student perspectives and the application of English language learning using ZTYPE games. The subjects of this study were 4th semester students of English education at Universitas Bhinneka PGRI, totalling 12 English students of Universitas Bhinneka PGRI. Researchers used descriptive qualitative research methods and used three instruments to obtain and collect data, namely: observation, interviews and questionnaires to students. The results of the application of ZTYPE games in vocabulary teaching are very good because it helps to understand vocabulary and new learning media for lecturers and students and can be applied so that they can understand each other's learning materials well. It is proven that the answers that have been obtained from English students when applying the learning, they have enthusiasm in improving vocabulary learning so that they pay attention to the lecturer's teaching style and consider it important for vocabulary learning at Universitas Bhinneka PGRI.